Renal function outcome after selective bladder-preserving tetramodality therapy consisting of maximal transurethral resection, induction chemoradiotherapy and consolidative partial cystectomy in comparison with radical cystectomy for patients with muscle-invasive bladder cancer: a two-centre retrospective study. (15th December 2022) - Fujiwara, Motohiro; Yokoyama, Minato; Toide, Masahiro; Fujiwara, Ryo; Tanaka, Hajime; Oguchi, Tomohiko; Komai, Yoshinobu; Yoshida, Soichiro; Matsuoka, Yoh; Numao, Noboru; Yamamoto, Shinya; Fukui, Iwao; et al.
Abstract: Objective: To compare renal function (RF) outcomes after bladder-preserving tetramodal therapy against muscle-invasive bladder cancer (MIBC) to those after radical cystectomy (RC). Methods: This study included 95 patients treated with tetramodal therapy consisting of transurethral bladder tumour resection, chemoradiotherapy and partial cystectomy (PC) and 300 patients treated with RC. The annual change in the estimated glomerular filtration rate (eGFR) was compared using the linear mixed model. Renal impairment was defined as a >25% decrease from the pretreatment eGFR, and renal impairment-free survival (RIFS) was calculated. The association between treatment type and renal impairment was assessed. Results: The number of patients who received neoadjuvant chemotherapy was 8 (8.4%) in the tetramodal therapy group and 75 (25.0%) in the RC group. After the inverse probability of treatment weighting adjustments, the baseline characteristics were balanced between the treatment groups. The mean eGFR before treatment in tetramodal therapy and RC groups was 69.4 and 69.6 mL/min/1.73 m 2 and declined with a slope of −0.7 and −1.5 mL/min/1.73 m 2 /year, respectively. The annual deterioration rate of post-treatment eGFR in the tetramodal therapy group was milder than in the RC group. The 5-year RIFS rate in the tetramodal therapy and the RC groups was 91.2 and 85.2%, respectively. Tetramodal therapy was an independent factor of better RIFS compared with RC. Conclusions: RF was better preserved after tetramodal therapy than after radical therapy; however, even after tetramodal therapy, the eGFR decreased, and a non-negligible proportion of patients developed renal impairment. Abstract : Renal function was better preserved after tetramodal therapy incorporating consolidative partial cystectomy than radical cystectomy in muscle-invasive bladder cancer patients.